Leonardo da Vinci’s “Old Paranoid Wall” in Surrealist Photography - Shik, Ida A. (Actual Problems of Theory and History of Art, 2016)
The article analyzes the key strategies of Leonardo da Vinci’s “old paranoid wall” representation in Surrealist photography and reveals their connections with the conceptual program of the Surrealist movement. The author marks tree main approaches to that problem in surrealist photography:1) extracting from the reality complete pictures/easy-interpreted forms showing how a wall texture participates in creation of the image;2) representation of the surface with the rich texture and chance images as an aesthetically- valuable object, close to abstraction;3) using the picturesque texture as a work element acquiring historical and cultural references.The author considers that working with the “old paranoid wall” motif the Surrealist photographers can find answers in the external world to the inner requests and explore the process of artistic creation and the role the chance plays in it as well. The author concludes that photographs representing the “old paranoid wall” motif actualize such key Surrealist conceptions as the marvelous, automatism, found object, paranoiac-critical method, principle of visual analogy. The author summarizes that the application of “Leonardo’s lessons” allows surrealist photographers to show that surreality is the immediate part of reality, which is yet to be uncovered and understood.
Keywords: Surrealism; Surrealist photography; chance image; the marvelous; automatism; found object; paranoiac-critical method; principle of visual analogy; surreality